If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1(4m + 6) = 3 + 4m + -13 Reorder the terms: 12 + -1(6 + 4m) = 3 + 4m + -13 12 + (6 * -1 + 4m * -1) = 3 + 4m + -13 12 + (-6 + -4m) = 3 + 4m + -13 Combine like terms: 12 + -6 = 6 6 + -4m = 3 + 4m + -13 Reorder the terms: 6 + -4m = 3 + -13 + 4m Combine like terms: 3 + -13 = -10 6 + -4m = -10 + 4m Solving 6 + -4m = -10 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 6 + -4m + -4m = -10 + 4m + -4m Combine like terms: -4m + -4m = -8m 6 + -8m = -10 + 4m + -4m Combine like terms: 4m + -4m = 0 6 + -8m = -10 + 0 6 + -8m = -10 Add '-6' to each side of the equation. 6 + -6 + -8m = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -8m = -10 + -6 -8m = -10 + -6 Combine like terms: -10 + -6 = -16 -8m = -16 Divide each side by '-8'. m = 2 Simplifying m = 2
| 2x^1/4=64/x | | 4z=-18.8 | | 0.8(x+50)+x=121 | | -3(5-t)=19 | | 5z-6-3z+2=0 | | 4h=19.6 | | -7/8y+4=-1/2y+1/4 | | 5x+6=2x-6 | | 58*x=0.33*58 | | 5x(x-7)=2x(3x+3) | | 14-1(6x-5)=5(2x-1)-4x | | 4+s=20 | | -22=2n-2-6 | | 9(a+4)+5a=-8(a+6) | | 6(4x+4)=216 | | 2436+2370= | | 6-(3y-6)=5-4y | | (x-3)+(5+x)+x=38 | | 7(2x-5)=-19x | | 6=x+6+5x | | 25x-1=24x | | W=1/5(x+y-z) | | 3t+8(2t-6)=2-48 | | 2.3(y-1)=1.4(y-10) | | 12-8x=168-43x | | 3(1x-2)=30 | | -5y=x+15 | | -3(x+2)-1=x+1 | | 5x+2+x+2+1/2x+2=58 | | 5x/6-2=7x/10 | | 2(n+4)=13n-25 | | -7(-3x-8)=308 |